Inflammation-fibrosis interplay in inflammatory bowel disease: mechanisms, progression, and therapeutic strategies - Li, Yanan; Xu, Feng; Fang, Yulai; Cui, Yuan; Zhu, Zhenxing; Wu, Yuguang; Tong, Yiheng; Hu, Jingyi; Zhu, Lei; Shen, Hong (Frontiers in Pharmacology, 2025)
BackgroundThe incidence of intestinal fibrosis in Inflammatory bowel disease has increased in recent years, and the repair process is complex, leading to substantial economic and social burdens. Therefore, understanding the pathogenesis of intestinal fibrosis and exploring potential therapeutic agents is crucial.PurposeThis article reviews the pathogenesis of IBD-related intestinal fibrosis, potential therapeutic targets, and the progress of research on Traditional Chinese Medicine (TCM) in inhibiting intestinal fibrosis. It also provides foundational data for developing innovative drugs to prevent intestinal fibrosis.MethodsThis article reviews the literature from the past decade on advancements in the cellular and molecular mechanisms underlying intestinal fibrosis. Data for this systematic research were obtained from electronic databases including PubMed, CNKI, SciFinder, and Web of Science. Additionally, a comprehensive analysis was conducted on reports regarding the use of TCM for the treatment of intestinal fibrosis. The study synthesizes and summarizes the research findings, presenting key patterns and trends through relevant charts.ResultsThis study reviewed recent advancements in understanding the cellular and molecular mechanisms of intestinal fibrosis, the active ingredients of TCM that inhibit intestinal fibrosis, the efficacy of TCM formulae in preventing intestinal fibrosis, and dietary modification that may contribute to the inhibition of intestinal fibrosis.ConclusionThis article examines the cellular and molecular mechanisms that promote the development of intestinal fibrosis, as well as potential therapeutic targets for its treatment. It also provides a theoretical basis for exploring and utilizing TCM resources in the management of intestinal fibrosis. Through the analysis of various TCM medicines, this article underscores the clinical significance and therapeutic potential of TCM and dietary modifications in treating intestinal fibrosis.